Proteins adsorbed to a polysulfone hemodialysis membrane under heparin and citrate anticoagulation regimens - Mares, Jan; Tuma, Zdenek; Moravec, Jiri; Pavlina, Richtrova; Matejovic, Martin (Artificial organs, 2019)
The study aim was to compare molecular-level effects (blood-dialyzer interactions) of heparin and citrate anticoagulation using proteome-wide analysis of biofilm adsorbed to dialysis membrane. Ten patients receiving maintenance hemodialysis were examined in a crossover design under three different anticoagulation regimens, namely citrate, heparin, and anticoagulation-free (control). Following a regular hemodialysis session (4 hours, polysulfone membrane), dialyzers were flushed and the surface biofilm eluted by acetic acid. Protein composition of the eluates was determined by 2-dimensional gel electrophoresis and resulting patterns compared between regimens. Proteins responsible for the difference were identified by mass spectrometry. Citrate anticoagulation was associated with significantly less protein adsorption to the membrane than heparin (2.2 [1.1-2.9] mg vs. 6.5 [2.9-11.6] mg, P = 0.009). Among the proteins identified as major discriminators between citrate and the other regimens, fibrin α-chain fragments of molecular weight below 40 kDa prevailed. In these fragments, an analysis of the amino acid sequence has been performed by comparison with the UniProt database. It showed missing α-chain cross-links. On the contrary, heparin prevented adsorption and cleavage of several heparin-binding proteins; especially complement factor H-related protein 3, insulin-like growth factor binding proteins (2, 4, and 5), and chemerin. Compared to heparin, citrate is associated with less protein adsorption and imperfectly crosslinked fibrin clot formation. Membrane adsorptive properties are significantly modified by the anticoagulation regimen.
Keywords: Polymers; polymery; heparin; senioři; membrány umělé; Anticoagulants; proteomika; adsorption; Male; Female; Proteomics; Aged; Middle Aged; Membranes, Artificial; sulfony; krevní proteiny; dialýza ledvin; Sulfones; hemokoagulace; mužské pohlaví; adsorpce; dialyzer; ženské pohlaví; antikoagulancia; citrate; fibrin; Renal Dialysis; Citric Acid; Blood Coagulation; lidé středního věku; Heparin; lidé; Humans; proteomics; Adsorption; Blood Proteins; kyselina citronová